2019
DOI: 10.1136/bmjqs-2019-010067
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between off-hours admissions for primary percutaneous coronary intervention, door-to-balloon time and mortality for patients with ST-elevation myocardial infarction in England: a registry-based prospective national cohort study

Abstract: BackgroundThe degree to which elevated mortality associated with weekend or night-time hospital admissions reflects poorer quality of care (‘off-hours effect’) is a contentious issue. We examined if off-hours admissions for primary percutaneous coronary intervention (PPCI) were associated with higher adjusted mortality and estimated the extent to which potential differences in door-to-balloon (DTB) times—a key indicator of care quality for ST elevation myocardial infarction (STEMI) patients—could explain this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In the cardiac literature, admission to a hospital for myocardial infarction over the weekend and during evenings is associated with significantly greater odds of 30-day mortality. 23 In our situation, while one could reasonably hypothesize that extended stays in the hospital following elective lumbar laminectomy would reduce the risk of some complications occurring in the postdischarge setting, it could also increase the risk of other complications, such as nosocomial infection. While further research is needed to evaluate the long-term consequences of prolonged LOS, our study finds no evidence to support the notion that patients fare better from a prolonged LOS while they remain in the hospital.…”
Section: Discussionmentioning
confidence: 84%
“…In the cardiac literature, admission to a hospital for myocardial infarction over the weekend and during evenings is associated with significantly greater odds of 30-day mortality. 23 In our situation, while one could reasonably hypothesize that extended stays in the hospital following elective lumbar laminectomy would reduce the risk of some complications occurring in the postdischarge setting, it could also increase the risk of other complications, such as nosocomial infection. While further research is needed to evaluate the long-term consequences of prolonged LOS, our study finds no evidence to support the notion that patients fare better from a prolonged LOS while they remain in the hospital.…”
Section: Discussionmentioning
confidence: 84%
“…This is in agreement with a large prospective observational study in England, which showed that after-hours admission was associated with a longer DTB time. 16 Our findings are unique as we were able to break down the components of DTB time to see which aspect was impacted. Based on our findings, we recommend that departments looking to improve after-hours DTB times focus on the processes after CVL lab activation such as movement of patients to the CVL as well as the call-back process for on-call CVL personnel.…”
Section: Other Factors Affecting Dtb Timementioning
confidence: 88%
“…For the predictors, we included factors that have been reported to be associated with DTB time, including age, sex, presentation during working hours, and ambulance usage. 15,16 Secondary outcomes include door-to-ECG time, door-to-activation time, activationto-lab time and lab-to-balloon time.…”
Section: Discussionmentioning
confidence: 99%
“…Following the example of the study by Bion et al, future studies could directly assess standards of care and the factors that most powerfully influence quality. A notable example is the study by Jayawardana and colleagues, 26 showing that the increased mortality for out-of-hours admissions with ST-elevation acute myocardial infarction was explained by differences in door-to-needle time, identifying the specific care process on which interventions should be targeted. To improve clinical practice, we Editorial need evidence that will help us design targeted interventions to influence the quality of care delivered and thereby patient outcomes.…”
Section: Should We Continue Studying the Weekend Effect?mentioning
confidence: 99%